Numerical Study of New Small-twist Tape Insert on Heat Transfer and Pressure Drop for Laminar Flow Inside Circular Pipe - Ng Y.L.; Alzakri A. (Penerbit Akademia Baru, 2024)
In this study, thermal performance of the laminar flow inside pipe with proposed small twisted tape insert is studied numerically by using computational fluid dynamic software. The proposed insert consists of three-and five-small twisted tapes insert that are arranged in radially symmetry pattern. These group of inserts are then arranged along the pipe with gap spacing S to generate continuous flow disturbance. The inserts are proposed to be modelled as zero-thickness layer to reduce the computational cost. The proposed zero-thickness model is validated by compare the with the results of 1mm-model and reference experimental results. The zero-thickness model is then implemented on the proposed insert design for numerical study. Compare with plain twisted tape insert, Nusselt number of the new design is increases by the range of approximately 0.07-42.7% for three-small tapes design, and 4.7-48.0% for five-small tapes design. Performance evaluation criteria (PEC) of present design ranging from 2.23.7 for three-small tapes design, and 2.65-3.65 for five-small tapes design. The proposed insert is found to have more advantage over plain twisted tape at lower Reynolds number, reflected by more significant increase in PEC at lower Reynolds number. From the result of friction factor and PEC, the optimum gap distance of insert group is found to be 50 mm. 2023, Penerbit Akademia Baru. All rights reserved.